Eksperimen Pengembangan Ragam Hias Keramik di Usaha Tembikar Lestari Deli Serdang - Sartika Yani Sinaga; Heri Soeprayogi; Mesra Amiruddin (Mahesa Research Center, 2020)
This study aims to develop a variety of decoration in the business of pottery business from the indicators of the principles of fine art that are carried out in Sustainable Pottery ceramics crafts on Jalan Medan Tanjung Morawa, Deli Serdang Regency. This research uses a development method. Data collection methods used are observation and documentation. The results of this study show the results of the development of ornamental variations on 10 samples of pottery produced by craftsmen, the authors made 10 decorative designs to develop decorative designs before, as a tangible result in this study an experimental action was carried out by researchers assisted by craftsmen by applying directly to pottery, The researcher chose 2 out of 10 development results and applied them directly to the pottery as a result of this study.